If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 + -3x + 1 = 0 Reorder the terms: 5 + 1 + 2x + -3x = 0 Combine like terms: 5 + 1 = 6 6 + 2x + -3x = 0 Combine like terms: 2x + -3x = -1x 6 + -1x = 0 Solving 6 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 3/8*10x | | 4log(4x+5)=-2 | | 5x-1-3=2 | | 3b-4-3b/2 | | 9x+4=10x+3 | | Log[4](3X)=3 | | 8(4y)-9(y)+1=0 | | -25=2v-7 | | 7=-7(v+2) | | 5x+5+2x-2=-4 | | 64/8/2 | | (8d^5)/4d^-3 | | 38=3u-10 | | 2a=-(1-a) | | 10x+2=6x+42 | | 6X^3+60X^2+96X-160=0 | | -6x=24+18x | | 5w+9=54 | | 5x+1+2x-1=-4 | | 7(x+6)-9(9x-5)=15 | | 9(x+2)-2(x-8)=14 | | lnx=sqrt(8-lnx^2) | | -4n=-9 | | y=ln(x)+c | | Ax(x-1)+B(x+1)(x-1)+C(x+1)x=x^2+4 | | -4b=11 | | 8x+2=4x-24 | | 11-6= | | -34=-2(3x+5) | | 6f+5(4f+3)= | | 6(2n+8)=102 | | 107=107(47-y) |